Formulasi Sediaan Sabun Cuci Tangan Ekstrak Daun Kelor (Moringa Oleifera L.) dan Efektivitasnya Sebagai Antiseptik - Amriani Sapra; Nur Khairi; Margaretha Margaretha; Andi Nur Aisyah; Maulita Indrisari; Fitriyanti Jumaetri; Noer Fauziah; Marwati Marwati (Jurnal Farmasi dan Ilmu Pengobatan, 2021)
Aim: The present research to formulate ethanol extract of Moringa oleifera leaf as a stable hand wash with required characteristics and evaluate it is effectivity against Escherichia coli and Staphylococcus aureus. Method: Moringa oleifera was extracted using 96% of ethanol. The obtained extract was formulated into hand wash in concentration 2.5; 5; and 7.5% w/v using surfactant sodium dodecyl sulfate and cocamide DEA. Obtained hand wash then evaluated the physical characteristics including organoleptic, pH, viscosity, relative mass, and foaming level. Hand wash effectivity evaluated against Escherichia coli and Staphylococcus aureus using diffusion method. Result: Hand wash of Moringa oleifera leaf extract fulfill the physical characteristics requirement and showing strong activity against E. coli. and S. aureus with average inhibition zone 13.1 mm; 13.8 mm; 14.5 mm; 12.9 mm; 15.16 mm; and 15.46 mm respectively for 2.5; 5; and 7.5% each. Conclusion: Overall, the experimental results revealed strong inhibition activity of M. oleifera hand wash to E. coli and S. aureus, but increasing the concentration of the extract has no significant different to inhibition activity.